Paradiplomacy for Educational Development: The Case of Jakarta and New South Wales - Muhammad; Daniel Christian Ariel Wibowo; Imaduddin Ahmad Hasibuan; Fathur Rahman (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
The cooperative relationship between Jakarta and New South Wales can be categorised as paradiplomacy, given that both are sub-state actors within their respective countries. By emphasising development in the education sector, both actors occupy an equal position and derive mutual benefit from this cooperation. This research aims to examine how the outcomes of collaboration between these two regions have contributed to the development of education in each. The research employs a qualitative method, using internet-based research as its data collection technique, drawing on scholarly articles, journals, and news reports. The findings indicate that paradiplomacy between the two regions has contributed to improved social welfare in the field of education for both sub-state actors, manifested in the exchange of knowledge, teaching staff, and scholarships, as well as expanded opportunities to develop the capabilities of young people in both regions.